2021
DOI: 10.4049/jimmunol.2001065
|View full text |Cite
|
Sign up to set email alerts
|

T Cells Specific for a Mycobacterial Glycolipid Expand after Intravenous Bacillus Calmette–Guérin Vaccination

Abstract: Intradermal vaccination with Mycobacterium bovis bacillus Calmette-Guérin (BCG) protects infants from disseminated tuberculosis, and i.v. BCG protects nonhuman primates (NHP) against pulmonary and extrapulmonary tuberculosis. In humans and NHP, protection is thought to be mediated by T cells, which typically recognize bacterial peptide Ags bound to MHC proteins. However, during vertebrate evolution, T cells acquired the capacity to recognize lipid Ags bound to CD1a, CD1b, and CD1c proteins expressed on APCs. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 72 publications
1
15
0
Order By: Relevance
“… 1 We characterized frequencies, phenotypic and functional characteristics of DURT cell populations in the peripheral blood following BCG vaccination to explore their potential as possible immunological targets for TB vaccination. Evidence that γδ T cells, MAIT, NKT and GEM T cells can respond to mycobacteria 15 , 43 , 44 , 45 , 46 , 47 provides a strong rationale to investigate if BCG vaccination can modulate these T cell populations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 1 We characterized frequencies, phenotypic and functional characteristics of DURT cell populations in the peripheral blood following BCG vaccination to explore their potential as possible immunological targets for TB vaccination. Evidence that γδ T cells, MAIT, NKT and GEM T cells can respond to mycobacteria 15 , 43 , 44 , 45 , 46 , 47 provides a strong rationale to investigate if BCG vaccination can modulate these T cell populations.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] A recent study in non-human primates also reported that glucose monomycolate (GMM)-specific CD1c-restricted T cells expanded after intravenous bacille Calmette-Guerin (BCG) administration. 11 Vaccination of guinea pigs with mycobacterial lipids formulated in liposomes was also associated with a reduction in the number of lesions, severity of pathology, and reduction of bacterial load upon challenge with M.tb. 12 Activation of MR1-restricted MAIT cells, which recognize vitamin B metabolites presented by the monomorphic MHC class 1-related molecule (MR1), has been shown in response to a variety of bacteria including BCG, Francisella tularensis, Klebsiella pneumonia, and M. tb.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The concept of vaccination is dependent on eliciting an adaptive immune response, B and T cells, from which memory cells will develop and provide long-lasting immunity. Although an immune response can happen as early as within the first week, long-lasting immunity can take up to 4 weeks to develop [ 2 , 3 ]. The BNT162b2 vaccine was shown to elicit an effective humoral (antibody-mediated) and cellular (T-cell-mediated) responses a week after the booster dose.…”
Section: Discussionmentioning
confidence: 99%
“…For example, some T cells that recognize mycolic acid derivatives, which are abundant in the mycobacterial cell wall, always express TCR-ɑ chains containing a rearrangement of the TCR-ɑ variable (TRAV)-1-2 and TCR-ɑ joining (TRAJ) 9 genes [ 10 ]. These cells are known as germline encoded mycolyl-reactive (GEM) T cells and are detectable at high-frequency in the blood of humans with latent and active TB as well as non-human primates after vaccination with BCG [ 11 , 12 ]. Because the GEM TCR-ɑ sequence is conserved across genetically unrelated individuals, quantitative detection should be possible without the need for deep-sequencing or advanced computational methods.…”
Section: Introductionmentioning
confidence: 99%